Perbedaan Keparahan Karies Gigi Molar Pertama Pada Anak Usia 6-9 Tahun Dengan 10-12 Tahun : Kajian Pada Radiograf Panoramik Di Rsgm-P Fkg Universitas Trisakti Periode 2017-2019 (Laporan Penelitian) - Alishia Fabiola Fattah Salma; Fatimah Boenjamin; Jeddy Jeddy (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: First permanent molars play very important roles in the oral cavity. Therefore, tooth loss of these teeth due to caries has major impacts on oral health in the future. Panoramic radiographs have been used routinely in the oral health examinations and have accuracy comparable to intraoral radiographs in detecting carious lesions of posterior teeth. There have been no studies regarding the difference in the severity of caries in first permanent molars using panoramic radiographs before in Indonesia. Objective:  The objective of this study was to determine the difference in the severity of first permanent molars caries in children aged 6-9 years and 10-12 years based on panoramic radiographs at the RSGM-P FKG Trisakti University for the period 2017-2019. Methods: The sample of this study were 680 panoramic radiographs of children aged 6-9 years and 10-12 RSGM-P FKG Trisakti University for the period 2017-2019. In this study, an ICCMS index was used to determine the severity of caries in first permanent molars. Result: The Mann Whitney U test used to determine the difference in the severity of caries showed that there was a difference in the caries severity of first permanent molars in children aged 6-9 years and 10-12 years (p <0.05). Conclusion: There was a difference in the caries severity of first permanent molars in children aged 6-9 years and 10-12 years based on panoramic radiographs at RSGM-P FKG Trisakti University for the period 2017-2019.